2014
DOI: 10.1108/ijchm-02-2013-0103
|View full text |Cite
|
Sign up to set email alerts
|

Does the importance of hotel attributes differ for senior tourists?

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…Nevertheless, it is possible to find a broad research framework on the profile of the repeat consumer in traditional tourist services, most of whom focus on touristic destinations [45][46][47][48][49][50][51][52][53]. There is less research on other sectors, such as hotels [54][55][56]. All these studies show the major influence of sociodemographic variables (such as education, gender, age, etc.).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Nevertheless, it is possible to find a broad research framework on the profile of the repeat consumer in traditional tourist services, most of whom focus on touristic destinations [45][46][47][48][49][50][51][52][53]. There is less research on other sectors, such as hotels [54][55][56]. All these studies show the major influence of sociodemographic variables (such as education, gender, age, etc.).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…A study from (Caber & Albayrak, 2014) findings shows that the value for money and the availability of organized entertainment in the hotel are the important attributes for the senior British tourist. As stated previously, every consumer has different preferences.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…(2) Demographic estimations reveal that the importance of the senior market has been growing to services industries, including tourism and hospitality, because the share of seniors in the world population is continuously increasing, and this trend is expected to be constant in the future. (3) The population of senior citizens has increased steadily over the past decades from 8% in 1950 to 11% in 2001 and is expected to reach 22% by 2050. (4) This suggests that worldwide the senior travellers market would become a substantial and increasingly important segment.…”
Section: Introductionmentioning
confidence: 99%
“…(9)(10) (10) Although "calendar age" is the most common criterion for distinguishing senior people, no consensus exists especially about when this period of life begins. (3) A number of researchers (11)(12)(13)(14) stated that seniors are people who are 55 years of age and above; other researchers (15)(16)(17)(18) suggested that people who are 50 years of age and above should be considered "seniors". Moreover, while some researchers (19) distinguished two categories of this age-group, namely pre-senior (between 50 and 64 years) and senior (≥ 65 years), the World Health Organisation (20) identified people aged ≥ 65 years as seniors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation